KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA BIG BOOK UNTUK SISWA KELAS RENDAH - Putri, Risna Estuning; Perdana, Ryzal; Pramudiyanti, Pramudiyanti (JS (JURNAL SEKOLAH), 2024)
Abstract: Media, particularly big books, serves as an effective support in low-grade classrooms. Various types of media have been developed to enhance the reading abilities of lower-grade students. The research method employed in this study involves a written survey where reading experts assess, evaluate, and formulate various writings. The findings from the research indicate that the use of large media significantly impacts the development of early reading skills. The primary objective of this research is to evaluate how the utilization of big book media can contribute to the improvement of early reading skills and to describe the developments in big book media observed in previous studies. Furthermore, the research results are compared to derive a final conclusion that the use of large media has a significant impact on early reading comprehension skills. This research highlights the success of involving big book media, taking into account the intelligence levels of students in lower grades. The main instrument in collecting this information is the analyst who compiles various studies in a research diary with points reflecting the subjects explored by specialists.Keyword: Beginning Reading, Elementary School, Big Book Abstrak: Media, khususnya big book, menjadi pendukung yang efektif dalam pembelajaran di kelas rendah. Berbagai jenis media telah dikembangkan untuk meningkatkan kemampuan membaca para siswa di kelas rendah. Metode penelitian yang digunakan dalam studi ini melibatkan survei tertulis di mana para ahli membaca, mengevaluasi, dan merumuskan berbagai tulisan. Temuan dari penelitian menunjukkan bahwa penggunaan media besar memiliki dampak yang signifikan terhadap perkembangan keterampilan membaca awal. Tujuan utama penelitian ini adalah untuk mengevaluasi bagaimana pemanfaatan media big book dapat berkontribusi pada peningkatan keterampilan membaca awal, serta untuk menggambarkan perkembangan media big book yang telah diamati dalam penelitian sebelumnya. Selanjutnya, hasil penelitian dibandingkan satu sama lain untuk mendapatkan kesimpulan akhir bahwa penggunaan media besar memiliki dampak yang signifikan pada keterampilan membaca pemahaman awal. Penelitian ini menyoroti keberhasilan melibatkan media buku besar mengingat tingkat kecerdasan siswa di kelas rendah. Alat utama dalam pengumpulan informasi ini adalah analis yang mencatat berbagai penelitian dalam buku harian riset dengan poin-poin yang mencerminkan subjek yang dijelajahi oleh para spesialis.Kata Kunci: Membaca permulaan, Sekolah Dasar, Big Book